One-Minute Sit-To-Stand Test: Reference Values for the Chilean Population - Jadue-Flores, L (Public Library of Science, 2025)
Introduction The one-minute sit to stand test (1min-STST) is a field test used to assess functional capacity. It is easily implementable and of significant clinical utility; however, no reference values are currently available for the Chilean population. The objective of this study was to establish reference values for the 1min-STST in a healthy Chilean population. Methods A multicenter cross-sectional study involving data collection from six locations in Chile was conducted. Healthy adults between 18 and 80 years of age were recruited. The anthropometric variables, levels of physical activity, smoking status, Borg scale ratings, and number of repetitions during the 1min-STST were recorded. Reference values were determined according to sex and age range. Results Four hundred ninety-nine healthy subjects (57.5% women, n = 287; median height, 1.63 (0.14) m; weight, 72.8 (20) kg; average BMI, 27.3 ± 4.1 kg/m2) were included in the study. The median (and the lower limit of normality (LLN) values) for the 1min-STST in men ranged from 18–29 years, with 38 (LLN 27) repetitions and 23 (LLN 15) repetitions for 70–80 years. For women aged 18–29 years, 38 (LLN 28) repetitions were performed, and for women aged 70–80 years, 24 (LLN 17) repetitions were performed. Conclusions This study established reference values for the healthy adult Chilean population. © 2025 Otto-Yáñez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.